MTCH2 promotes adipogenesis in intramuscular preadipocytes via an m(6)A-YTHDF1–dependent mechanism - Jiang, Qin (FASEB J, 2019)
Intramuscular fat is considered a potential factor that is associated with meat quality in animal production and insulin resistance in humans. N(6)-methyladenosine (m(6)A) modification of mRNA plays an important role in regulating adipogenesis. However, the effects of m(6)A on the adipogenesis of intramuscular preadipocytes and associated mechanisms remain unknown. Here, we performed m(6)A sequencing to compare m(6)A methylome of the longissimus dorsi muscles (LDMs) between Landrace pigs (lean-type breed) and Jinhua pigs (obese-type breed with higher levels of intramuscular fat). Transcriptome-wide m(6)A profiling of porcine LDMs was highly conserved with humans and mice. Furthermore, we identified a unique methylated gene in Jinhua pigs named mitochondrial carrier homology 2 (MTCH2). The m(6)A levels of MTCH2 mRNA were reduced by introducing a synonymous mutation, and adipogenesis test results showed that the MTCH2 mutant was inferior with regard to adipogenesis compared with the MTCH2 wild-type. We then found that MTCH2 protein expression was positively associated with m(6)A levels, and an YTH domain family protein 1–RNA immunoprecipitation–quantitative PCR assay indicated that MTCH2 mRNA was a target of the YTH domain family protein 1. This study provides comprehensive m(6)A profiles of LDM transcriptomes in pigs and suggests an essential role for m(6)A modification of MTCH2 in intramuscular fat regulation.—Jiang, Q., Sun, B., Liu, Q., Cai, M., Wu, R., Wang, F., Yao, Y., Wang, Y., Wang, X. MTCH2 promotes adipogenesis in intramuscular preadipocytes via an m(6)A-YTHDF1–dependent mechanism.